FAMILY RELATIONS IN DIDACTIC WORKS AS A GUARANTEE OF FAMILY STRENGTH - Qahhorov , Siddiq Qahhorovich; Izbullayeva, Gulchehra Valeriyevna (Educational Research in Universal Sciences, 2022)
This article describes family relationships in didactic works created in Central Asia in the 13th century. In particular, the role of husband and wife in maintaining the stability of the family in the relationship between husband and wife, a statement of female loyalty, and its importance today.